Writing history through the hammer: an analysis of knowledge production through the South African auction houses - Maharaj, Arisha (My University, 2021)
This research will be examining the South African fine art auction houses, which make up the local secondary art market. There is currently very limited research on the local secondary market and the existing studies are largely done from a quantitative perspective on the economic value of art. This has created a knowledge gap for a qualitative study. The aim of this research is to locate the position of the art historical knowledge produced through the art auctions and motivate the placement of this historical knowledge in the larger landscape, as it comes from the bias perspective of a business. Through secondary research and an in-depth study into the functions and objectives of the local auction houses, the ways in which art historical knowledge is produced will be determined and its placement in the larger historical landscape will be argued. Drawing on the concepts of discourse, representation, cultural capital and power and knowledge from theorists Stuart Hall and Pierre Bourdieu, this will provide the theoretical framework for the research.
A research report submitted in partial fulfillment of the requirements of the degree of Masters of Arts in History, University of Witwatersrand, 2021